The study on low temperature sintering of nano-tungsten powders. (December 2016) - Ren, Chai; Fang, Z. Zak; Zhang, Huan; Koopman, Mark
Abstract: Ultrafine grain tungsten is a promising candidate for plasma facing component applications in future fusion reactors. The conventional press-and-sinter powder metallurgy method is a preferred route for producing ultrafine grain tungsten from nanosize tungsten powders. However, controlling grain growth, while simultaneously attempting to achieve maximum densification, has been a challenge for making UGF tungsten by sintering. In this study, the effect of processing parameters on the densification and grain growth of nano-W powders was investigated. Near-fully densified tungsten was obtained at sintering temperatures between 1100 and 1300 °C, and both Ar and H2 sintering atmospheres were investigated. The Ar sintering atmosphere was determined to more favorably promote densification and minimize grain growth. The nanosized tungsten powder compacts were subjected to reduction in H2 as a part of the sintering cycle. The reduction temperature was found to have significant effects on the sintering of nano-W powder, primarily as a result of grain coarsening, which was seen at temperatures as low as 700 °C. Highlights: Near-fully densified tungsten was obtained by sintering nano-powders at 1100–1300 °C. The Ar sintering atmosphere was found to yield better densification and less grain growth than in H2 atmosphere. Reduction temperature was found to affect both the sintered density and grain size.